CERTAIN REPRODUCTIVE CHARACTERISTICS OF THE ELECTRIC CATFISH (Malapterurus electricus, Gmelin, 1789) IN OVIA RIVER, SOUTHERN NIGERIA - OBOH, P. I; MEGWAI, O.M. (Nigerian Journal of Fisheries, 2016)
The sex composition, gonad morphology and maturation, gonadosomatic index (GSI) and fecundity of Malapterurus electricus were studied for a period of six months (May to October, 2014) in Ovia River, Nigeria. Three hundred and thirty-two (332) fish specimens comprising of 147 males and 185 females were examined giving a male to female ratio of 1:1.26. Paired gonads were revealed in both sexes; and four and five gonad maturation stages were observed for males and females respectively. Mean GSI was 0.27±0.24 SD in males and 5.92±6.82 SD in females. Fully matured ovaries were observed from May to September with GSI varying from 7.85 to 15.52. Fecundity varied between 218 and 3216 eggs with an average of 705.42±411.09 SD and it correlated significantly (P<0.001) only with ovary weight. The mean condition factor index (1.39) of the fish population of M. electricus showed that the fishes were in good condition to grow and reproduce.